2018
DOI: 10.1093/annonc/mdx483
|View full text |Cite
|
Sign up to set email alerts
|

Tracking evolution of aromatase inhibitor resistance with circulating tumour DNA analysis in metastatic breast cancer

Abstract: Cancers progressing on the first-line AI show high levels of genetic heterogeneity, with frequent sub-clonal mutations. Sub-clonal KRAS mutations are found at high frequency. The genetic diversity of AI resistant cancers may limit subsequent targeted therapy approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 18 publications
3
95
0
4
Order By: Relevance
“…It has been shown that ESR1 mutant cells retain their dependence on CDK4/6 and cyclin D; thus, CDK4/6 inhibitors seem to be active in ESR1 mutant cells [36]. Since data from patients in the second-line setting (PALOMA-3, Bolero-2, SofEA trials) [20,21,29] provide evidence that fulvestrant is superior to AI in ESR1-mutated patients, it seems that fulvestrant combined with CDK4/6 will be more efficacious in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ESR1 mutant cells retain their dependence on CDK4/6 and cyclin D; thus, CDK4/6 inhibitors seem to be active in ESR1 mutant cells [36]. Since data from patients in the second-line setting (PALOMA-3, Bolero-2, SofEA trials) [20,21,29] provide evidence that fulvestrant is superior to AI in ESR1-mutated patients, it seems that fulvestrant combined with CDK4/6 will be more efficacious in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 Thirty patients exhibited polyclonal Y537S and D538G mutations, and other studies have also confirmed that ESR1 mutations are frequently polyclonal. 9,28,[34][35][36][37] Survival analyses showed that patients with Y537S or D538G mutations exhibited worse overall survival compared with patients who had only WT ER (32.1 vs 20.7 months). Patients with polyclonal Cancer November 1, 2019 ESR1 mutations also exhibited a worse overall survival (15.2 months).…”
Section: Ddpcr Detection Of Esr1 Mutations In Patient Biopsiesmentioning
confidence: 99%
“…Abundant evidence has confirmed that quantification of mutant circulating tumor DNA (ctDNA) is valuable in cancer diagnosis, prognositication, monitoring therapy response, and postoperative recurrence (4)(5)(6). Emerging studies are also reported its application in tracking clonal evolution and elucidating treatment-resistant mechanisms (7,8).…”
Section: Introductionmentioning
confidence: 99%